Susceptibility Provision Enhances Effective De-escalation (SPEED): utilizing rapid phenotypic susceptibility testing in Gram-negative bloodstream infections and its potential clinical impact. (25th January 2019) - Schneider, Jack G; Wood, James B; Schmitt, Bryan H; Emery, Christopher L; Davis, Thomas E; Smith, Nathan W; Blevins, Sarah; Hiles, Jon; Desai, Armisha; Wrin, Justin; Bocian, Brittany; Manaloor, John J
Abstract: Objectives: We evaluated the performance and time to result for pathogen identification (ID) and antimicrobial susceptibility testing (AST) of the Accelerate Pheno™ system (AXDX) compared with standard of care (SOC) methods. We also assessed the hypothetical improvement in antibiotic utilization if AXDX had been implemented. Methods: Clinical samples from patients with monomicrobial Gram-negative bacteraemia were tested and compared between AXDX and the SOC methods of the VERIGENE ® and Bruker MALDI Biotyper ® systems for ID and the VITEK ® 2 system for AST. Additionally, charts were reviewed to calculate theoretical times to antibiotic de-escalation, escalation and active and optimal therapy Results: ID mean time was 21 h for MALDI-TOF MS, 4.4 h for VERIGENE ® and 3.7 h for AXDX. AST mean time was 35 h for VITEK ® 2 and 9.0 h for AXDX. For ID, positive percentage agreement was 95.9% and negative percentage agreement was 99.9%. For AST, essential agreement was 94.5% and categorical agreement was 93.5%. If AXDX results had been available to inform patient care, 25% of patients could have been put on active therapy sooner, while 78% of patients who had therapy optimized during hospitalization could have had therapy optimized sooner. Additionally, AXDX could have reduced time to de-escalation (16 versus 31 h) and escalation (19 versus 31 h) compared with SOC. Conclusions: By providing fast and reliable ID and AST results, AXDX has the potential to improve antimicrobial utilization and enhance antimicrobial stewardship.